2006
DOI: 10.1099/vir.0.81595-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage cultures are susceptible to lytic productive infection by endothelial-cell-propagated human cytomegalovirus strains and present viral IE1 protein to CD4+ T cells despite late downregulation of MHC class II molecules

Abstract: The contribution of CD4+ T cells to control of human cytomegalovirus (HCMV) has been shown and infected tissue macrophages might contribute to this response by antigen presentation. As shown previously, CD4 + T cells recognize HCMV immediate-early antigen IE1 on glioblastoma cells manipulated to express MHC class II molecules. Here, the possible interference of virus-induced MHC class II downmodulation with the presentation of IE1 by natural target cells was analysed. The capacity of IE1-specific CD4 + T-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Endothelial cells were infected at a multiplicity of infection (MOI) of 5 or 20 or mock infected with medium alone. This endothelial cell-tropic strain of HCMV also efficiently infects monocytes (81), as does our Towne/E strain (84,85,103). We found that 100% of the endothelial cells and 100% of monocytes were infected with TB40-UL32-HCMV/E and Towne/E when we used an MOI of 5 or an MOI of 20.…”
Section: Methodsmentioning
confidence: 99%
“…Endothelial cells were infected at a multiplicity of infection (MOI) of 5 or 20 or mock infected with medium alone. This endothelial cell-tropic strain of HCMV also efficiently infects monocytes (81), as does our Towne/E strain (84,85,103). We found that 100% of the endothelial cells and 100% of monocytes were infected with TB40-UL32-HCMV/E and Towne/E when we used an MOI of 5 or an MOI of 20.…”
Section: Methodsmentioning
confidence: 99%
“…These model systems support HCMV latent infection, and importantly, the latent virus can be reactivated, producing infectious progeny (12,14,16,50,55,56). However, these primary cell systems are hampered by finite cell numbers coupled with lower infectivity rates, limited life span ex vivo, donor variation, the complexity of a heterogeneous population, and the inability to exploit current molecular biology tools to manipulate gene expression.…”
mentioning
confidence: 99%
“…Ex vivo latency models that utilize primary CD34 ϩ /CD38 Ϫ hematopoietic progenitor cells (HPCs) isolated from bone marrow or umbilical cord blood (13,14,26,35,42), as well as peripheral blood monocytes (7,16,27,33,50,52,56,58,67), represent perhaps a more complete assessment of HCMV latency. These model systems support HCMV latent infection, and importantly, the latent virus can be reactivated, producing infectious progeny (12,14,16,50,55,56).…”
mentioning
confidence: 99%
“…While HCMV infection is usually clinically unapparent in the immunocompetent host, it can cause severe disseminated infections under conditions of immunosuppression, with manifestations in the lung, retina, and gastrointestinal tract, among others (12). Various cell types support viral replication, including epithelial cells and endothelial cells (ECs), smooth muscle cells, fibroblasts, and cells of hematopoietic origin (13,14,18,19,25,26,37). Among these target cells, endothelial cells are assumed to contribute particularly to hematogenous dissemination of HCMV (24).…”
mentioning
confidence: 99%